2016
DOI: 10.28978/nesciences.286240
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Biodiversity Effects in Turkish Seas

Abstract: Sea temperature change in the Mediterranean, Marmara and Black Sea coasts of Turkey and its possible biodiversity effects are investigated. The surface sea water temperatures of the Mediterranean, Marmara and Black Sea region of Turkey for last 41 years showed increased trends in Mediterranean Sea (Iskenderun, Mersin and Antalya), Marmara Sea (Istanbul) and Black Sea (Samsun). On the other hand, the number of Indo-Pacific species is getting rapidly increased for the last decade that caused increased invasion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 18 publications
1
44
0
2
Order By: Relevance
“…Şimşek et al (2013) examined annual and seasonal trends in meteorological data in Hatay (Turkey) and reported that all seasons have increasing trends excluding the winter season. Turan et al (2016) investigated changes in sea surface temperature (SST) and possible effects on the biodiversity in the Turkish coasts of the Mediterranean, Marmara and Black Sea. They found that SST for all seas have increasing trends.…”
Section: Discussionmentioning
confidence: 99%
“…Şimşek et al (2013) examined annual and seasonal trends in meteorological data in Hatay (Turkey) and reported that all seasons have increasing trends excluding the winter season. Turan et al (2016) investigated changes in sea surface temperature (SST) and possible effects on the biodiversity in the Turkish coasts of the Mediterranean, Marmara and Black Sea. They found that SST for all seas have increasing trends.…”
Section: Discussionmentioning
confidence: 99%
“…The origin analysis draws attention that the most part of the species are of Atlantic originated cold-water fish species (Figure 6). It is thought that due to its high rate of cold water species, the biodiversity of the Black Sea would likely be affected by water temperature rises as a result of global climate changes in future as reported by Turan et al (2016). Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…In the president study, A. djedaba is reported as second Indo-Paficic species in the Black Sea since the first Indo-Pacififc species Sphyraena obtusata was given by Boltachev (2009). The increase in water temperature has been considered as a main reason for the increasing entry of Indo-Pacific species in the Mediterranean Sea (Ben Rais Lasram et al, 2010;Golani, 2010;Turan et al 2016). Turan et al (2016) reported that there is an increased trend of temperature for the Black Se due to global climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Turan et al (2016) reported that there is an increased trend of temperature for the Black Se due to global climate change. Turan et al (2016) also indicated that the increased trend of temperature may increase the number of Mediterranean Atlantic and lessepsian fish species in the Black Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation